2020
DOI: 10.1108/ijbpa-10-2019-0090
|View full text |Cite
|
Sign up to set email alerts
|

BIM business value for asset owners: key issues and challenges

Abstract: PurposeThere is a need to develop the understanding of asset owners concerning the constraints of building information modelling (BIM) implementation, and its subsequent value realisation activities in asset management (AM) cannot be overstated. This is because the life cycle cost of a built asset is three times more than construction costs and five times more than the initial investment outlays. Hence, this paper investigated and identified the key issues and challenges of realising BIM business value in AM.D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…More precise characteristics of BIM commitment have been uncovered by Olugboyega and Windapo (2019), which define BIM commitment as the whole dedication of construction organisations' top management to BIM adaption, adoption, application and execution. Investigations such as Munir et al (2020) and Sinoh et al (2020) have highlighted top management commitment as a significant driving force for BIM adoption, lending support to the argument for BIM commitment as an essential component of a BIM implementation strategy. Based on this context, this study develops a hypothesis stating that BIM commitment is important for increasing the proportion of BIM adoption (Hypothesis 3).…”
Section: Conceptualising the Four-wheel Model Of Bim Implementationmentioning
confidence: 93%
See 1 more Smart Citation
“…More precise characteristics of BIM commitment have been uncovered by Olugboyega and Windapo (2019), which define BIM commitment as the whole dedication of construction organisations' top management to BIM adaption, adoption, application and execution. Investigations such as Munir et al (2020) and Sinoh et al (2020) have highlighted top management commitment as a significant driving force for BIM adoption, lending support to the argument for BIM commitment as an essential component of a BIM implementation strategy. Based on this context, this study develops a hypothesis stating that BIM commitment is important for increasing the proportion of BIM adoption (Hypothesis 3).…”
Section: Conceptualising the Four-wheel Model Of Bim Implementationmentioning
confidence: 93%
“…More precise characteristics of BIM commitment have been uncovered by Olugboyega and Windapo (2019), which define BIM commitment as the whole dedication of construction organisations' top management to BIM adaption, adoption, application and execution. Investigations such as Munir et al. (2020) and Sinoh et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While the relative advantages of BIM enabled BIM adoption, the complexity of BIM was deemed as a critical inhibitor [54]. The intense manual evaluation suggested that complex BIM adoption circumstances, such as complexities of building characteristics [55] and work processes [56], contractual chal-lenges [57,58], interoperability trends [59], risk factors [55], political and organizational contexts [60,61], dynamics of drivers [62], and emergencies [63], have drawn the interest of many researchers. For instance, Mayouf et al [56] elicited implications of shortfalls impacting 5D BIM adoption as well as complexities facing quantity surveyors within BIM processes in the United Kingdom's construction industry.…”
Section: Qualitative Evaluationmentioning
confidence: 99%
“…Case studies prove that manual data entry in COBie and the required format structures delay the integration process [8,9,60]. This is perhaps why several studies [14,81] have advocated that some of the pressing future research areas should encompass mapping a seamless process for data exchange for BIM and O&M.…”
Section: Interoperability and Information Logistics In The Execution ...mentioning
confidence: 99%